2020
DOI: 10.1186/s12935-020-01600-5
|View full text |Cite
|
Sign up to set email alerts
|

ZBTB7A, a potential biomarker for prognosis and immune infiltrates, inhibits progression of endometrial cancer based on bioinformatics analysis and experiments

Abstract: Backgroud ZBTB protein is an important member of the C2H2 zinc finger protein family. As a transcription factor, it is widely involved in the transcriptional regulation of genes, cell proliferation, differentiation, and apoptosis. The ZBTB7A has been largely linked to different kinds of tumors due to its diverse function. However, the value for ZBTB7A in uterine corpus endometrial carcinoma (UCEC) is unclear. Methods In our work, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The reduced ZBTB7A level in endometrial cancer was observed in analyses using the UALCAN and Oncomine databases and was validated with the GEPIA database [49]. In addition, the overexpression of LGR5 and SST in endometrial cancer reported with the Oncomine database was also confirmed with GEPIA.…”
Section: Gepia Databasesupporting
confidence: 56%
See 3 more Smart Citations
“…The reduced ZBTB7A level in endometrial cancer was observed in analyses using the UALCAN and Oncomine databases and was validated with the GEPIA database [49]. In addition, the overexpression of LGR5 and SST in endometrial cancer reported with the Oncomine database was also confirmed with GEPIA.…”
Section: Gepia Databasesupporting
confidence: 56%
“…Similarly, Geng et al used the Oncomine database to assess the expression of Zinc finger and BTB domain-containing protein 7A (ZBTB7A). Significant reduction in mRNA expression and DNA copy number variation of ZBTB7A was noted in endometrial cancer compared to the control [49]. This is a valuable observation, as ZBTB7A is considered an oncogene that may constitute a potential therapeutic target.…”
Section: Oncomine Databasementioning
confidence: 71%
See 2 more Smart Citations
“…The Zbtb1 family consists of a different set of transcription factors, and Zbtb1 plays an important role in lymphocyte development ( Zhu et al., 2018 ). The Zbtb protein family also plays an important role in cancer, such as in the relationship between Zbtb7 and endometrial cancer cells and bladder cancer cells ( Guo et al., 2017 ; Geng et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%